2000
DOI: 10.1001/archopht.118.11.1489
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Topical Cyclosporine Treatment of Patients With Dry Eye Syndrome<subtitle>Effect on Conjunctival Lymphocytes</subtitle>

Abstract: To study the effect of topical cyclosporine on lymphocyte activation within the conjunctiva of patients with moderate to severe dry eye syndrome (Sjö gren and non-Sjö gren).Methods: Biopsy specimens were obtained at baseline and after 6 months of cyclosporine treatment from eyes of 32 patients with moderate to severe dry eye syndrome; 19 were cyclosporine treated (0.05% cyclosporine, n = 13; 0.1% cyclosporine, n = 6) and 13 were vehicle treated. Within this group there were 12 with Sjö gren syndrome and 20 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
165
0
11

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 301 publications
(181 citation statements)
references
References 30 publications
5
165
0
11
Order By: Relevance
“…Elevated levels of this marker have been found in dry eye patients. 25 Treating dry eyes with artificial tears has proven to reduce the expression of these inflammatory markers, 26 which could be a consequence of the increased stability of the tear film upon increasing the TBUT and of the subsequent reduction in hyperosmolarity that the lubricant treatment produces. Our study indicates an increase in HLA-DR and CD3 after cataract surgery, which is insignificant in the case of HLA-DR.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of this marker have been found in dry eye patients. 25 Treating dry eyes with artificial tears has proven to reduce the expression of these inflammatory markers, 26 which could be a consequence of the increased stability of the tear film upon increasing the TBUT and of the subsequent reduction in hyperosmolarity that the lubricant treatment produces. Our study indicates an increase in HLA-DR and CD3 after cataract surgery, which is insignificant in the case of HLA-DR.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid systemic side effects, topical treatment with cyclosporin A eye drops has been investigated for dry eye, but its efficacy for dry eye associated with cGVHD remains to be clarified. 5,19 It is possible that autologous serum eye drops may have functioned as a topical treatment with immunosuppressants in patients who received systemic immunosuppressants. However, this possibility is difficult to confirm, because patients on systemic immunosuppressants tend to have more severe dry eye.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 It was shown that the topical antiinflammatory treatment of dry eye patients brought to a significant reduction of the numbers of activated lymphocytes within the conjunctiva, so demonstrating the potential usefulness of an anti-inflammatory treatment for dry eye. 6 The treatment of ocular surface inflammation can be helpful to improve symptoms of ocular discomfort in patients with SS. Nonsteriodal anti-inflammatory drugs (NSAIDs) could be considered a good alternative to steroids in order to avoid all the complications of steroidal therapy in the treatment of patients with chronic diseases such as SS.…”
Section: Introductionmentioning
confidence: 99%